Fly ash-based grouting fire extinguishing material and application thereof

Optimize the proportion of fly ash-based grouting materials through the response surface method, solve the problem of unsatisfactory grouting effect in the self-ignition treatment of slag rock mountain, achieve efficient fire extinguishing and slope reinforcement, and ensure the environmental restoration of slag rock mountain and the prevention and control of geological disasters. effect.

CN119258477APending Publication Date: 2025-01-07HEBEI HUAKAN GEOLOGICAL EXPLORATION CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411448286.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing research has failed to effectively combine the unique environmental factors of the slag mountain, and ignored the interaction between fly ash-based slurry components, resulting in unsatisfactory grouting and fire extinguishing effects and difficulty in taking into account environmental benefits and geological disaster prevention and control.

Method used

The model is constructed through the response surface method, and the water-cement ratio, cement dosage and exciter dosage of fly ash-based grouting materials are optimized, the optimal ratio is determined, the diffusion radius, stone rate and compressive strength of the stone body are improved, and the suitable one is formed. Materials for self-ignition control of slag piles.

Benefits of technology

It has achieved efficient fire extinguishing effect and reinforcement of slag hill slopes. The error between the test value and the prediction value is less than 5%, which is in line with the expectation of mining environmental recovery, taking into account the stability of the dispersion slope and the prevention and control of geological disasters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258477A_ABST
    Figure CN119258477A_ABST
Patent Text Reader

Abstract

The invention discloses a fly ash-based grouting fire extinguishing material and application thereof, and belongs to the technical field of fire extinguishing materials, the fire extinguishing material comprises the following raw materials: water, fly ash, cement and an exciting agent, the mass ratio of the water to the fly ash is 0.7-0.9, the mass of the cement is 15-25% of the sum of the mass of the water and the fly ash, the mass of the exciting agent is 10-20% of the total mass of the water and the fly ash, and the mass of the exciting agent is 10-20% of the total mass of the fly ash. The mass of the exciting agent is 15-25% of the sum of the mass of the water and the fly ash. According to the method, the stone rate, the diffusion radius and the stone body compressive strength are selected as evaluation indexes, then the optimal range of three factors including the water cement ratio, the cement mixing amount and the exciting agent mixing amount is preliminarily drawn up through a single-factor test, and a response curved surface method is used for constructing a response curved surface model to determine the interaction among the factors; the proportion of the fly ash-based fire-extinguishing grouting material is optimized, and the fly ash-based grouting fire-extinguishing material with the diffusion radius, the stone rate and the stone body compressive strength is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fire extinguishing materials, and in particular relates to a fly ash-based grouting fire extinguishing material and application thereof. Background Art

[0002] Gangue heaps are places where coal mines and coal preparation plants concentrate gangue. Solid wastes in gangue heaps include stripped gangue, coal tunnel gangue, rock tunnel gangue, hand-selected gangue, and coal preparation plant tailings. Spontaneous combustion, explosion, landslides, and leaching water from gangue heaps all pollute the mining environment.

[0003] Backfill grouting technology is one of the important means of controlling and preventing spontaneous combustion of waste rock heaps. Currently, commonly used base materials include cement, clay, gel, foam, fly ash, etc. Among them, fly ash base material slurry has the advantages of low cost, low heat generation, and good diffusion through ratio optimization. Fly ash is the fine ash collected from the flue gas after coal combustion. Fly ash is the main solid waste discharged by coal-fired power plants. The main oxide composition of fly ash in my country's thermal power plants is: SiO 2 、Al 2 O 3 ,FeO,Fe 2 O 3 , CaO, TiO 2 wait.

[0004] At present, researchers mainly verify the applicability of fly ash-based slurry in gangue mountain fire extinguishing projects through experimental grouting and optimization of physical and chemical properties. Wen Lei and others studied the use of alkaline fly ash as the main raw material for grouting fire extinguishing of gangue mountains. The temperature in the hole can be reduced to 80°C in practice. The idea of ​​"waste treatment" for spontaneous combustion of gangue mountains was summarized. Practice has proved that the filling effect of the base material has good environmental and economic benefits; Jin Dapeng completed the preparation and physical and chemical performance analysis of fly ash-based grouting fire extinguishing materials, and analyzed the influence of performance indicators such as fluidity, viscosity and water separation rate on the cooling and fire extinguishing effect. The optimal raw material ratio suitable for each performance is: water / ash ratio 0.7, fly ash content 70%, lime content 20%, and water glass accounting for 6% of cement mass fraction. Many studies have found that fly ash-based slurry is a good filling fire extinguishing material. Based on this, studying the optimal slurry ratio under different evaluation indicators and applying it to production practice has become the next research focus.

[0005] At present, most studies are limited to the single factor analysis of the physical and chemical properties of fly ash-based slurry, which fails to combine the unique environmental factors of the waste rock mountain and ignores the interaction between components. The waste rock mountain is a bulk structure with a certain degree of instability. The high porosity provides the oxygen channel required for spontaneous combustion. After spontaneous combustion, the bulk structure is affected by the burning of the waste rock and its stability is reduced, and it is prone to landslide geological disasters. Therefore, ideal diffusion and good pore filling rate are necessary conditions for achieving good cooling and fire extinguishing effects during the implementation of the grouting fire extinguishing process. At the same time, the environmental benefits should also be taken into account to strengthen the bulk structure of the spontaneous combustion waste rock mountain to prevent slope geological disasters. Summary of the invention

[0006] In response to the technical problems raised in the background technology, the present invention selects stone rate, diffusion radius, and stone body compressive strength as evaluation indicators, and then preliminarily proposes the optimal ranges of the three factors of water-cement ratio, cement content, and activator content through single factor experiments. The response surface model is constructed using the response surface method to determine the interaction between the factors, and the ratio of fly ash-based fire extinguishing grouting materials is optimized to obtain a fly ash-based grouting fire extinguishing material with diffusion radius, stone rate, and stone body compressive strength.

[0007] The present invention is achieved through the following technical solutions:

[0008] A fly ash-based grouting fire extinguishing material comprises the following raw materials: water, fly ash, cement and an activator, wherein the mass ratio of water to fly ash is 0.7-0.9, the mass of the cement is 15%-25% of the total mass of the water and the fly ash, and the mass of the activator is 15%-25% of the total mass of the water and the fly ash.

[0009] In the above technical solution, the activator is obtained by mixing slaked lime and sodium sulfate in a mass ratio of 7:3.

[0010] In the above technical solution, the mass ratio of water to fly ash is preferably 0.76, the mass of the cement is preferably 19.2% of the sum of the mass of water and fly ash, and the mass of the activator is preferably 17.9% of the sum of the mass of water and fly ash.

[0011] A fly ash-based grouting fire extinguishing material is used in the spontaneous combustion control and prevention of waste rock piles. The fire extinguishing material has a diffusion radius of 2.31m, a stone rate of 97.1%, and a stone body compressive strength of 7.35Mpa.

[0012] Beneficial effects:

[0013] The present invention proposes a fly ash-based grouting fire extinguishing material, the water-cement ratio of the fire extinguishing material is 0.76, the cement content is 19.2%, the activator content is 17.9%, the diffusion radius of the fire extinguishing material is 2.31m, the stone rate is 97.1%, and the stone body compressive strength is 7.35Mpa. Through model verification, the error between the test value and the predicted value is less than 5%, indicating that the model has high accuracy. At the same time, after actual engineering verification, the grouting fire extinguishing effect under this mix ratio meets the expectations of mine environmental restoration and takes into account the reinforcement requirements of bulk slopes. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in describing the embodiments are briefly introduced below.

[0015] Figure 1 Statistical chart (I) showing the effect of water-cement ratio on the performance of fly ash-based slurries.

[0016] Figure 2 Statistical chart (II) showing the effect of water-cement ratio on the performance of fly ash-based slurry.

[0017] Figure 3 Statistical graph (III) showing the effect of water-cement ratio on the performance of fly ash-based slurry.

[0018] Figure 4 Statistical chart (I) showing the effect of cement content on the performance of fly ash-based slurry.

[0019] Figure 5 Statistical chart (II) showing the effect of cement content on the performance of fly ash-based slurry.

[0020] Figure 6 Statistical chart (III) showing the effect of cement content on the performance of fly ash-based slurry.

[0021] Figure 7 Statistical chart (I) showing the effect of activator dosage on the performance of fly ash-based slurry.

[0022] Figure 8 Statistical chart (II) showing the effect of activator dosage on the performance of fly ash-based slurry.

[0023] Fig. 9 Statistical chart (III) showing the effect of activator dosage on the performance of fly ash-based slurry.

[0024] Fig.10 The response surface and contour plot of the interaction effect of two factors on the slurry diffusion radius (a).

[0025] Fig.11 The response surface and contour plot of the interaction effect of two factors on the slurry diffusion radius (b).

[0026] Fig.12 The response surface and contour plot of the interaction effect of two factors on the slurry diffusion radius (c).

[0027] Fig.13 The response surface and contour plots of the interaction between the two factors on the serous stone rate (A).

[0028] Fig.14 The response surface and contour plots of the interaction between the two factors on the serous stone rate (B).

[0029] Fig.15 The response surface and contour plots for the effect of the interaction between the two factors on the serous stone rate (III).

[0030] Fig.16 The response surface and contour plot of the interaction effect of two factors on the compressive strength of slurry stones (a).

[0031] Fig.17 The response surface and contour plot of the interaction effect of two factors on the compressive strength of slurry stones (II).

[0032] Fig.18 The response surface and contour plots of the interaction between the two factors on the compressive strength of slurry stones (III). DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0034] Description of factors affecting slurry

[0035] (1) Determination of diffusion radius

[0036] The diffusion degree of fly ash-based slurry in the bulk accumulation of coal gangue under specific engineering conditions directly determines the layout spacing of the drilling project and the grouting fire extinguishing effect, and plays a vital role in controlling the project cost.

[0037] The actual diffusion radius is often difficult to obtain in field tests. Therefore, in the treatment process, due to the unclear law of the effective diffusion range of the slurry, it becomes very challenging to reasonably determine the spacing between grouting holes, which in turn affects the smooth progress of fire extinguishing. In this study, finite element numerical simulation was used to determine the diffusion radius of each ratio of slurry in the simulation field.

[0038] (2) Stone rate

[0039] The slurry stone rate refers to the proportion or degree of stone formation in the slurry during grouting construction. Reasonable control of the slurry stone rate can improve the filling effect, enhance the stability of the structure, and reduce the risk of geological disasters such as landslides.

[0040] During this study, the solidification rate was experimentally measured, and the stone rate was obtained by measuring the volume of the slurry before solidification V1 and the volume of the block after solidification V2.

[0041] (1)

[0042] (3) Compressive strength

[0043] The compressive strength of the stone body reflects the bearing capacity of the slope after grouting. At the same time, there is a positive correlation between the compressive strength and the internal friction angle of the slope. The anti-slip stability of the slope can be improved by controlling the strength.

[0044] In this experiment, coal gangue was collected on-site in the study area and mixed with different groups of slurries in a 1:1 ratio to make 7cm×7cm×7cm test blocks. They were uniformly naturally cured for 28 days, and data were obtained through a mild compressive test.

[0045] Example 1 Single factor experiment

[0046] Through single factor test, the effects of powder-water-cement ratio (factor A), cement content (factor B), and activator (factor C, slaked lime: sodium sulfate (mass ratio) = 7:3) on fly ash slurry stone rate, diffusion radius, and stone body compressive strength were studied, so as to preliminarily formulate the optimal content range of the three factors. The slurry water-cement ratio is 0.6~1.0, and the cement content and activator content are both 10%~30%, (that is, the cement content means that the mass of cement is 10%~30% of the mass sum of water and fly ash, and the activator content means that the mass of activator is 10%~30% of the mass sum of water and fly ash, the same below). The specific mix ratio and test results are shown in Table 1.

[0047] Table 1 Single factor experimental mix ratio scheme and performance test results of fly ash-based slurry Sample No. water / ashratio Cement Activator Diffusion radius (m) Stonerate (%) Compressive strength (Mpa) A1 0.8 20 10 2.91 94.8 6.78 A2 0.8 20 15 2.68 95 6.82 A3 0.8 20 20 2.30 96.5 7.01 A4 0.8 20 25 1.91 96.3 7 A5 0.8 20 30 1.85 95.6 6.87 C1 0.8 10 20 2.70 94.6 6.32 C2 0.8 15 20 2.62 94.9 6.51 C3 0.8 20 20 2.30 96.5 7.01 C4 0.8 25 20 1.72 97.3 7.38 C5 0.8 30 20 1.68 97.4 7.41 W1 0.6 20 20 1.89 97.6 7.73 W2 0.7 20 20 2.07 97.4 7.45 W3 0.8 20 20 2.30 96.5 7.01 W4 0.9 20 20 2.55 95.7 6.52 W5 1 20 20 2.71 86.1 5.65

[0048] Analysis of fly ash-based slurry performance under single factor

[0049] (1) Effect of water-cement ratio on the performance of fly ash-based slurry

[0050] Figure 1-3 The figure shows the changes of slurry performance screening indicators under different water-cement ratios. As can be seen from the figure, with the increase of water-cement ratio, the slurry stone rate gradually decreases. When the water-cement ratio is less than 0.9, the stone rate can be maintained at a high level of more than 95%. After the water-cement ratio exceeds 0.9, the stone rate drops sharply. When the water-cement ratio is 1.0, the stone rate is only about 85%. The influence of water-cement ratio on diffusion radius and compressive strength index is generally monotonic linear distribution. Therefore, considering economic factors comprehensively, the water-cement ratio range in the experiment is determined to be 0.7-0.9.

[0051] (2) Effect of cement content on the properties of fly ash-based slurry

[0052] Figure 4-6 The statistical results of the influence of different cement dosages on the slurry performance screening indicators. As can be seen from the figure, with the increase of cement dosage, the overall hydration reaction in the slurry is enhanced, and the mutual adhesion and friction between the particles will increase the viscosity of the slurry, resulting in a decrease in the diffusion radius. The slurry stone rate and compressive strength are positively correlated with the cement dosage, but due to the concentration of hydration products, too high or too low cement dosage has a negative impact on the efficiency of improving the stone rate and compressive strength. The performance improvement efficiency is highest when the dosage range is 15%~25%, and the unit dosage increases the stone rate and strength by 0.24% and 0.087Mp; the unit dosage in the production range exceeding 25% increases the stone rate and strength by only 0.02% and 0.006Mp, which does not meet the requirements of engineering economy. Therefore, after comprehensive consideration, the optimal cement dosage range in subsequent tests is determined to be 15%~25%.

[0053] (3) Effect of activator dosage on the performance of fly ash-based slurry

[0054] Figure 7-9 The statistical results of the influence of different activator dosages on the slurry performance screening indicators are shown. The addition of activators increases the Ca(OH) 2 and SiO 2 ratio, destroying the Si-O-Si and Si-O-Al-network structures on the surface of the glass in the fly ash, generating hydrated calcium silicate and hydrated calcium aluminate with good gelling effect and promoting hydration reaction. As can be seen from the figure, the diffusion radius of the fly ash-based slurry gradually decreases with the increase of the activator dosage. This is because the hydration reaction is enhanced, the viscous material component gradually increases, and the viscosity of the system is increased. The stone rate and compressive strength show a trend of first increasing and then decreasing with the increase of the activator dosage. In this experiment, when the activator dosage reaches 20%, the stone rate and compressive strength reach peak values ​​of 96.5% and 7.01Mpa. This is because the increase of Ca(OH) within an appropriate range 2 、,Na 2 SO 4 The content accelerates the excitation speed and promotes the activity of fly ash to generate hydrates to increase the stone rate and strength. However, excessive addition will cause an imbalance in the excitation reaction. Ca(OH) 2 、,Na 2 SO 4 The excess of the product hydrated calcium sulfoaluminate (AFt) will have a negative effect on the stone rate and compressive strength. Therefore, considering comprehensively, the optimal dosage range of the activator is 15%~25%.

[0055] Example 2 Response surface methodology experimental design

[0056] The single factor test shows that the water-cement ratio, cement content and activator content have a great influence on the performance of fly ash-based slurry, and the optimal content range of these three influencing factors is obtained. The water-cement ratio, cement content and activator content are selected as influencing factors, marked as X1, X2 and X3 respectively. According to the results of the previous single factor test, the selection of each factor level is listed in detail in Table 2. The Box-Behnken with three factors, three levels and three center points was designed using DesignExpert10 software. A total of 17 groups of experiments were arranged. Each group of experiments used the diffusion radius, stone rate and stone body compressive strength as the response values, marked as Y1, Y2 and Y3 respectively. The test results of each response value are shown in Table 2.

[0057] Table 2 Response surface test design scheme and performance test results of fly ash-based slurry Sample No. water / ashratio Cement(%) Activator(%) Diffusion radius (m) Stonerate (%) Compressive strength (Mpa) 1 0.7 25 20 1.63 97.5 7.51 2 0.9 20 15 2.70 94.7 6.63 3 0.9 15 20 2.67 94.2 5.79 4 0.9 20 25 2.37 95.1 6.37 5 0.7 15 20 2.33 96.2 7.11 6 0.8 20 20 2.30 96.7 7.02 7 0.8 20 20 2.30 96.5 7.01 8 0.7 20 15 2.29 96.6 7.27 9 0.8 20 20 2.30 96.4 7.05 10 0.9 25 20 2.23 96.4 7 11 0.7 20 25 1.96 96.9 7.23 12 0.8 20 20 2.30 96.6 7.02 13 0.8 15 25 2.11 92.9 6.13 14 0.8 25 25 1.60 96.7 7.17 15 0.8 20 20 2.30 96.4 7.08 16 0.8 25 15 1.57 97.9 7.44 17 0.8 15 15 2.71 93.7 6.27

[0058] 1. Optimization results and analysis of influence surface method

[0059] (1) Model fitting

[0060] The response surface methodology was used to perform multivariate regression fitting on the relationship between the diffusion radius, stone rate and compressive strength of fly ash-based slurry and the three influencing factors of water-cement ratio, cement content and activator content. The regression models of diffusion radius Y1, stone rate Y2 and compressive strength Y3 were obtained, as shown in equations (2) to (4). The variance analysis results of the regression models of each response value are shown in Table 3.

[0061] Y 1 =2.3+0.22X 1 -0.348X 2 -0.1537X 3 +0.065X 1 X 2 +0.1578X 2 X 3 +0.1237X 1 X 1 -0.2087X 2 X 2 -0.0937X 3 X 3 (2)

[0062] Y 2 =96.5-0.85X 1 +1.44X 2 -0.1625X 3 +0.225X 1 X 2 +0.025X 1 X 3 -0.1X 2 X3 +0.05X 1 X 1 -0.475X 2 X 2 -0.725X 3 X 3 (3)

[0063] Y 3 =7.03-0.4163X 1 +0.4775X 2 -0.0887X 3 +0.2025X 1 X 2 -0.055X 1 X 3 -0.0325X 2 X 3 -0.0175X 1 X 1 -0.14X 2 X 2 -0.1175X 3 X 3 (4)

[0064] Table 3 Variance analysis of the regression model for the diffusion radius of fly ash-based slurry Source Sum of Squares MeanSquare F-value p-value Note Model 1.94 0.216 42.8 <0.0001 significant A 0.3872 0.3872 76.73 <0.0001 B 0.973 0.973 192.81 0.0003 C 0.1891 0.1891 37.47 0.0005 AB 0.0169 0.0169 3.35 0.0109 AC 0.0745 0.1792 12.66 0.02 BC 0.0992 0.0992 19.66 0.003 A² 0.0645 0.0645 12.78 0.009 B² 0.1835 0.1835 36.36 0.0005 C² 0.037 0.037 7.33 0.0303 Residual 0.0353 0.005 - - Lack of Fit 0.0353 0.0118 - - Not significant R² 0.9822

[0065] Table 4 Variance analysis of regression model for stone rate of fly ash-based slurry Source Sum of Squares MeanSquare F-value p-value Note Model 26.09 2.9 5.82 0.015 significant A 5.78 5.78 11.6 0.0113 B 16.53 16.53 33.18 0.0007 C 0.2112 0.2112 0.424 0.0437 AB 0.2025 0.2025 0.4065 0.0235 AC 0.0025 0.0025 0.005 0.0399 BC 0.04 0.04 0.0803 0.0358 A² 0.0105 0.0105 0.0211 0.0523 B² 0.95 0.95 1.91 0.2098 C² 2.21 2.21 4.44 0.073 Residual 0.0349 0.049 - - Lack of Fit 0.0349 0.0016 - - Not significant R² 0.9441

[0066] Table 5 Analysis of variance of regression model for mild compression resistance of fly ash-based slurry agglomeration Source Sum of Squares MeanSquare F-value p-value Note Model 3.61 0.4007 46.65 <0.0001 significant A 1.39 1.39 161.38 0.0005 B 1.82 1.82 212.36 <0.0001 C 0.063 0.063 7.34 0.0303 AB 0.164 0.164 19.1 0.0033 AC 0.0121 0.0121 1.41 0.0274 BC 0.0042 0.0042 0.4919 0.0405 A² 0.0013 0.0013 0.1501 0.7099 B² 0.0825 0.0825 9.61 0.0173 C² 0.0581 0.0581 6.77 0.0353 Residual 0.0601 0.0086 - - Lack of Fit 0.0601 0.02 - - Not significant R² 0.9836

[0067] When evaluating the significance of the model, the goodness of fit test (R² test) was used. The R² coefficient value reflects the degree of difference between the response surface and the true value, and its value range is 0 to 1. When R² is equal to 1, it means that the two are completely consistent. We judge the significance of each factor in the model by the coefficient P value, where P<0.05 indicates that the factor is significant, and P<0.01 indicates that the factor is very significant. From the results of Tables 3 to 5, the P values ​​of the three evaluation index models are all less than 0.05, indicating that the regression effect of the model is significant. This means that the diffusion radius, stone rate and compressive strength of the fly ash-based slurry have a good fit with the predicted value, so the model can be effectively used for the analysis and prediction of the response value. In addition, the lack of fit terms (Lack of Fit) of each model did not show significance, which further verified the high fitting accuracy and strong reliability of the model. The regression coefficients R² of the fly ash-based slurry diffusion radius, stone rate, and stone compressive strength were 0.9822, 0.9441, and 0.9836, respectively, which confirmed that the regression model had a high degree of fit and was suitable for the analysis and prediction of various indicators.

[0068] (2) The impact of the interaction of various factors on the response value

[0069] According to Tables 3 to 5, 1) The water-cement ratio, cement content and activator content have extremely significant effects on the diffusion degree of fly ash-based slurry. Among them, the interaction between cement content and activator content also shows an extremely significant effect on the slurry diffusion radius, while the interaction between the other two groups is significant. The order of influence of each factor and interaction term on slurry diffusion is: A>B>C>BC>AB>AC. 2) The single effect of cement content on the stone rate of fly ash-based slurry is extremely significant, while the effects of water-cement ratio and activator content on the stone rate of slurry show significant effects. The interaction of the two factors has significant effects on the stone rate of slurry, and the order of influence of each factor and interaction term on the stone rate of slurry is: B>A>AB>BC>AC>C. 3) The single factors of cement content and water-cement ratio have extremely significant effects on the compressive strength of the stone body of fly ash-based slurry, while the effect of activator content on the compressive strength of the stone body is significant. The interaction between water-cement ratio and cement content also has a significant effect on the compressive strength of slurry stones. The order of influence of each factor and interaction term on the compressive strength of slurry stones is: B>A>AB>AC>C>BC.

[0070] According to the Box-Behnken regression model, the response surface curves and contour plots of the diffusion radius, stone rate and stone compressive strength of fly ash-based slurry were drawn to intuitively analyze the influence of the interaction of various factors on the performance of fly ash-based slurry. The results are as follows: Figures 10 to 18 shown.

[0071] Figure 10-12The response surface and contour map of the interaction of two factors on the diffusion radius of the slurry. It can be seen from the figure that the influence of each single factor on the diffusion radius of the fly ash-based slurry is monotonic. The diffusion radius increases with the increase of the water-cement ratio, while the cement content and the activator content have a side effect on the increase of the diffusion radius. Among them, the response surface of the interaction between cement and activator content is steep and the contour lines are dense, indicating that their interaction has a significant effect on the slurry diffusion radius. When the cement content is 19.1% and the activator content is 16.6%, the slurry diffusion radius reaches a peak value of 2.73m. This is mainly due to the decrease in cement and activator content, the weakening of the system hydration reaction, and the reduction in the concentration of colloidal particles in the slurry, which changes the rheological properties of the slurry, thereby reducing the slurry diffusion resistance and improving the diffusion capacity. Figure 13-15 It can be seen that: when the water-cement ratio is 0.7 and the cement content increases from 15% to 20%, the slurry stone rate increases by 5.7%; when the cement content is 25% and the water-cement ratio decreases from 0.9 to 0.7, the fly ash-based slurry stone rate increases by 1.6%. This shows that the interaction between the water-cement ratio and the cement content has a significant effect on the fly ash-based slurry stone rate. This is because a higher cement content and a lower water-cement ratio within an appropriate range increase the concentration of hydration reactants, which is conducive to the forward reaction. The concentration of hydration products (such as hydrated calcium silicate, calcium hydroxide, etc.) increases, thereby increasing the fly ash-based slurry stone rate. Figure 16-18 It can be seen that when the water-cement ratio is 0.9, as the cement content increases, the compressive strength of the stone body increases significantly, while when the water-cement ratio is 0.7, as the cement content increases, the compressive strength of the stone body increases less, and the interaction is obvious. This is because when the water-cement ratio is small, increasing the cement content can reach the hydration reaction equilibrium and saturation state faster, and the strength improvement is small. Therefore, when the water-cement ratio increases, more cement needs to be added to improve the strength loss, resulting in a larger increase in compressive strength.

[0072] 2. Verification of Optimization Results of Response Surface Methodology

[0073] Taking the maximization of the diffusion radius of fly ash-based grouting fire extinguishing materials, the highest value of the stone rate, and the maximum compressive strength of the stone body as the optimization objectives, the Design Expert 14 software was used to optimize the mix ratio of fly ash-based grouting materials, and the optimal mix ratio was 0.76 water-cement ratio, 19.2% cement content, and 17.9% activator content. At this time, the slurry diffusion radius was 2.31m, the stone rate was 97.1%, and the stone body compressive strength was 7.35Mpa. Considering the effectiveness of the response surface model, the predicted values ​​and experimental values ​​of the model were compared, as shown in Table 6. It can be seen that the errors between the experimental values ​​and the predicted values ​​of the diffusion radius, stone rate, and compressive strength are all less than 5%, indicating that the model has high accuracy.

[0074] Table 6 Comparison of experimental values ​​and predicted values ​​for optimal mix design Form Diffusion radius (m) Stone rate (%) Compressive strength (Mpa) Predicted value 2.31 97.1 7.35 Experimental value 2.28 96.3 7.27 Error / % 1.29 0.82 1.09

[0075] Example 3 Study on the flow field diffusion of composite slurry

[0076] 1. Diffusion radius simulation analysis

[0077] Slurry fluidity is an important indicator for evaluating the fluidity of slurry, which has a significant impact on the quality, efficiency and safety of grouting construction. In the layout of exploration projects, the degree of diffusion of slurry in bulk materials is a key factor. However, the actual diffusion radius is often difficult to obtain in field tests. Therefore, in the treatment process, due to the unclear law of the effective diffusion range of slurry, it becomes very challenging to reasonably determine the spacing between grouting holes, which in turn affects the smooth progress of fire extinguishing.

[0078] To address this problem, we derived a theoretical calculation formula for the grouting radius of the waste rock pile based on the principles of fluid mechanics and calculus calculation methods. At the same time, we used COMSOL software combined with Darcy's law for simulation analysis and obtained the grouting radius of the waste rock pile. Through the calculated grouting radius, the spacing between grouting holes was scientifically and rationally determined, and the plum blossom pile alternating layout was adopted to ensure that there were no dead corners in the grouting process. This method can effectively improve the effect and safety of grouting construction.

[0079] (5)

[0080] After obtaining the mathematical model of the grouting radius and determining the numerical simulation calculation method, we used two calculation methods to evaluate the grouting radius of a waste rock pile. First, the specific parameters were substituted into the theoretical calculation formula to calculate the results, and then COMSOL was used for numerical simulation calculation, and the results obtained by the two methods were compared and analyzed.

[0081] Taking a waste rock mountain as an example, a grouting pipe with a diameter of 108mm and a length of 12m was selected. The dynamic viscosity of the slurry is 0.025Pa·s, the density is 1170kg / m³, and the grouting rate is 27m³ / h. Considering that the porosity between the waste rocks is 0.3 and the permeability is 1.4×10⁻ 9 m², and the grouting pressure is set to 2.0MPa. Substituting these values ​​into the theoretical calculation formula, the grouting radius is R=2.12m; and through the numerical simulation calculation of COMSOL, the effective grouting radius under the same conditions is R=2.1m. By comparing and analyzing the results of these two calculation methods, we can have a more comprehensive understanding of the relationship between the actual effect of the grouting process and the theoretical prediction.

[0082] Through comparative analysis, we found that the difference between the two calculation results is not significant. The main reason for the error is that when processing the COMSOL numerical simulation calculation results, the part where only one side diffuses or a small amount of slurry diffuses is discarded. In addition, the gravity of the slurry is not taken into account in the numerical calculation process, resulting in the simulation results being relatively idealized and therefore low. The errors of the two calculation results are within the allowable range, so we can take the smaller value of 2.1m in the two calculation methods as the effective radius of grouting in the waste rock pile under this condition.

[0083] 2. Application Verification

[0084] Through scientific calculations, the grouting radius of a waste rock heap under known conditions was determined to be 2.1m. Based on this grouting radius, we can set the hole spacing of each row of grouting holes to 4.2m or 4m. Considering that the diffusion range of the slurry is cylindrical, in order to ensure that the slurry can fully cover the entire fire area, it is recommended that each hole in the latter row of grouting holes be arranged between the two grouting holes in the previous row to form a staggered arrangement of plum blossom piles. This layout can not only ensure that the slurry covers every position in the fire area and avoid leaving grouting dead corners, but also minimize the number of grouting holes while ensuring the grouting effect, thereby effectively reducing construction costs. After the construction was completed, we conducted multiple temperature monitoring, and the results showed that the temperature in the fire area had dropped below 70°C, successfully achieving the purpose of extinguishing the fire on the waste rock heap.

[0085] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A fly ash-based grouting fire extinguishing material, characterized in that: The method comprises the following raw materials: water, fly ash, cement and activator, wherein the mass ratio of water to fly ash is 0.7-0.9, the mass of cement is 15%-25% of the total mass of water and fly ash, and the mass of activator is 15%-25% of the total mass of water and fly ash.

2. A fly ash-based grouting fire extinguishing material according to claim 1, characterized in that: The activator is obtained by mixing slaked lime and sodium sulfate in a mass ratio of 7:

3.

3. The fly ash-based grouting fire extinguishing material according to claim 1, characterized in that: The mass ratio of water to fly ash is 0.76, the mass of the cement is 19.2% of the total mass of water and fly ash, and the mass of the activator is 17.9% of the total mass of water and fly ash.

4. A fly ash-based grouting fire extinguishing material is used in the spontaneous combustion control and prevention of waste rock heaps, characterized in that: The diffusion radius of the fire extinguishing material is 2.31m, the stone rate is 97.1%, and the compressive strength of the stone body is 7.35Mpa.

Citation Information

Cited By

  • Ecological restoration method for acidic coal gangue dump

    CN120634008A